Royal Police Ordinances in Early Modern Sweden : the Emergence of Voluntaristic Understanding of Law. - Kotkas, Toomas (Leiden : Brill, 2013)
In Royal Police Ordinances in Early Modern Sweden, based on analysis of a large amount of empirical material Toomas Kotkas claims that a new, voluntaristic understanding of law emerged in 17th-century Sweden.
Political theory and police in early modern Sweden -- Royal police ordinances between 1523 and 1611 : enforcement of medieval law -- Royal police ordinances between 1612 and 1718 : making of new law -- Scientification of police: the end of the broad conception of police -- Conclusions.
Print version record.
Includes bibliographical references and index.
English.
eBooks on EBSCOhost
Keywords: Police -- Sweden -- History; LAW -- Administrative Law & Regulatory Practice; Police; Sweden; History